Autogenic Relaxation Therapy To Reduce Mother Anxiety - Nani, Desiyani; Setiyani, Rahmi (Jurnal of Community Health Development, 2021)
Abstract Parents who have children with mental retardation often experience anxiety disorders due to inadequate feelings about care. One popular modality therapy is an autogenic relaxation technique that aims to overcome the symptoms of physical and mental disorders. Based on data on the number of people with mental retardation in Banyumas Regency, 225 children have mental retardation. Banyumas Special School of Yakut and Kuncup Mas Banyumas has 63 students with mental retardation. Health education and training in autogenic relaxation therapy is given to parents of mentally retarded children who attend the Yakut Special School. An indicator of decreased anxiety by measuring the physiological responses of participants' bodies before and after therapy. After autogenic relaxation therapy for participants there was a decrease in respiratory frequency of 0.6%, a decrease in pulse rate of 3.05%, a decrease in systolic blood pressure of 6.4%, and a decrease in diastolic blood pressure of 3.5%.